The Arrábida Chain: the Alpine Orogeny in the Vicinity of the Atlantic Ocean - Fonseca, André (2021)
The Arrábida Chain is one of the finest structural examples of the Alpine orogeny in Portugal. Placed along the south-western coast of the Setubal Peninsula, it presents one of the most spectacular coastal geomorphological settings in Portugal, with vertical sea cliffs with over 150 m plunging into the Atlantic Ocean. Due to its geographical position, post-Miocene landscape evolution was essentially a response to base-level change imposed by Neogene sea-level fluctuations, tectonic uplift of the Arrábida Chain and subsidence of the lower Tagus basin. Strong contrasts in bedrock erodibility played a crucial role in landscape evolution by imposing limits to drainage network incision, leaving competent rock bodies in clear association to the highest sector of the chain.